Hoshin Kanri for The Lean Enterprise. Developing Competitive Capabilities and Managing Profit - JACKSON, Thomas L (Produktivity press, 2006)
Hoshin Kanri for The Lean Enterprise. Developing Competitive Capabilitiews and ...